Transient effects of corridors on polygyne fire ants over a decade. (1st December 2022) - Resasco, Julian; Burt, Melissa A.; Orrock, John L.; Haddad, Nick M.; Shoemaker, DeWayne; Levey, Douglas J.
Abstract: Although corridors are frequently regarded as a way to mitigate the negative effects of habitat fragmentation, concerns persist that corridors may facilitate the spread of invasive species to the detriment of native species. The invasive fire ant, Solenopsis invicta, has two social forms. The polygyne form has limited dispersal abilities relative to the monogyne form. Our previous work in a large‐scale corridor experiment showed that in landscapes dominated by the polygyne form, fire ant density was higher and native ant species richness was lower in habitat patches connected by corridors than in unconnected patches. We expected that these observed corridor effects would be transient, that is, that fire ant density and native ant species richness differences between connected and unconnected patches would diminish over time as fire ants eventually fully established within patches. We tested this prediction by resampling the three landscapes dominated by polygyne fire ants 6 to 11 years after our original study. Differences in fire ant density between connected and unconnected habitat patches in these landscapes decreased, as expected. Differences in native ant species richness were variable but lowest in the last 2 years of sampling. These findings support our prediction of transient corridor effects on this invasive ant and stress the importance of temporal dynamics in assessing population and community impacts of habitat connectivity. Abstract : Resasco et al. examine the effects of habitat corridors on polygyne fire ants ( Solenopsis invicta ) and native ants in a large‐scale experiment over a decade. Their findings show transient corridor effects on this invasive ant and stress the importance of temporal dynamics in assessing population and community impacts of connectivity.